Medical laboratory science review - Harr, Robert R. (F.A. Davis, 2013)
A resource to gain the theoretical and practical knowledge you need to be prepared for classroom tests and certification and licensure examinations. With an overview of test-taking skills and techniques, it helps you build your knowledge with more than 3,200 multiple-choice questions - over 2,100 in the text and more than 1,000 on the CD-ROM